Digital Literacy Revolution: The Role of Artificial Intelligence (AI) Technology in Personalizing Learning and Improving Students’ Literacy Competency - Fujiono; Seful Bahri; Yuliana Trisanti (Universitas Islam Negeri Palopo, 2026)
The digital era of the 21st century has brought a fundamental transformation in the global education landscape, where Artificial Intelligence (AI) technology has emerged as a key catalyst in the contemporary learning revolution that demands comprehensive digital literacy. This study aims to analyze the role of AI technology in revolutionizing digital literacy through learning personalization and its impact on improving student literacy competencies in a holistic and multidimensional manner. The research method uses a qualitative approach with systematic literature review referring to the PRISMA guide, analyzing 30 high-quality articles from the Scopus, Web of Science, IEEE Xplore, and Emerald Insight databases for the 2020-2024 period through thematic synthesis. The results of the study revealed that AI technology plays a transformative role in personalizing learning through an adaptive system that analyzes individual characteristics, cognitive preferences, and student learning patterns, thereby significantly increasing engagement and achievement of learning outcomes. The implementation of AI expands the dimensions of digital literacy to include cognitive, technical, ethical, evaluative, creative, communicative, social, and metacognitive aspects in an integrated framework. The conclusion shows that AI has great potential to create an adaptive and inclusive education ecosystem, but faces infrastructure challenges, educators' digital competencies, and ethical issues. It is recommended to develop a gradual implementation strategy, investment in professional development, and a comprehensive ethical framework for optimizing the use of AI in education.